The experiences of at-risk adolescent girls in group therapy, cofacilitated by a psychotherapist and music therapist: a pilot study - Braham, David L., author; MacPhee, David, 1954-, advisor; Lyness, Kevin P., committee member; Davis, William B. (William Barron), committee member (Colorado State University. Libraries, 2005)
This study bridges the gap between psychotherapy and music therapy. Based on the experiential essence of musical interventions, it is hypothesized that the inclusion of music therapy in the context of adolescent group psychotherapy may enhance the therapeutic process. At-risk adolescent girls age 14-18 participated in the study. Both quantitative and qualitative data was collected. Pre-and post-tests were administered to each participant using the Therapeutic Factors Inventory (TFI; Lese & MacNair-Semands, 2000), and descriptive information was collected through informal interviews following the 6-week intervention. While the TFI showed little promise in identifying the therapeutic factors contributing the outcomes due to a small sample size (n=3), qualitative data supports the use of music as an influential and significant contribution to group psychotherapy with at-risk adolescents.
Keywords: Group psychotherapy; Teenage girls; Music therapy